Cytological features of lung adenocarcinoma with massive lymphocyte infiltration - Álvarez-Rodríguez, F (Medknow Publications & Media Pvt Ltd, 2012)
Adenocarcinoma with massive lymphocyte infiltration is a rare pulmonary neoplasm with few reported cases. It seems to have a better outcome than conventional adenocarcinomas, but it is still not clear if it constitutes a specific clinicopathological entity. We report a case in which cytological studies were available. The small size of the tumor, abundant lymphocyte population, well-differentiated morphology of the neoplasm and scarcity of atypical cells resulted in a difficult cytological diagnosis. This entity should be considered when evaluating pulmonary lesions with abundant lymphocytes. Not all carcinomas with prominent lymphoid stroma show the high-grade, pleomorphic morphology of lymphoepithelioma-like carcinomas.